(untitled) (Archives of Criminology, 2023)
The study examines the development of crime statistics in Hungary. Data on registered crimes have been collected since 1968 using the same methodology. The long-term analysis reveals several trends. The first period, 1968–1989, was characterised by slow growth. The second phase started after the regime change: 1990–2000. There was a very significant increase and strong waves in the data. In the third phase, in the decade following the new millennium, the data appear to have stabilized at around 400,000 cases per year. Starting in 2012, a new trend of dramatic decline has emerged in the crime data. The study examines the evolution and possible causes of these diverse trends. It presents the social and political changes behind the trends. Particular emphasis will be placed on examining the causes of the period of the transformation from communism to liberal democracy and current trends. These are the most exciting stages of Hungarian criminal statistics. The relationship between social change and the evolution of the criminal situation is the basic question. A significant and lasting decrease in the number of registered crimes is a new phenomenon that has not been seen in processes since 1968. The number of registered crimes has decreased significantly in recent years. In analysing the causes behind this decrease, the combined effect of several factors can be detected. The most significant decrease was caused by the amendment of the legal regulations, modifying the legal situation of document abuse and raising the threshold for infringement. In addition, there is a downward trend at the international level. Significant emigration in recent years has also contributed to a reduction in the number of registered crimes.